Unveiling the role of histone deacetylases in neurological diseases: focus on epilepsy - Dan-Feng Cao; Xin-Yu Zhou; Qian Guo; Ming-Yao Xiang; Mei-Hua Bao; Bin-Sheng He; Xiao-Yuan Mao (Biomarker Research)
Abstract Epilepsy remains a prevalent chronic neurological disease that is featured by aberrant, recurrent and hypersynchronous discharge of neurons and poses a great challenge to healthcare systems. Although several therapeutic interventions are successfully utilized for treating epilepsy, they can merely provide symptom relief but cannot exert disease-modifying effect. Therefore, it is of urgent need to explore other potential mechanism to develop a novel approach to delay the epileptic progression. Since approximately 30 years ago, histone deacetylases (HDACs), the versatile epigenetic regulators responsible for gene transcription via binding histones or non-histone substrates, have grabbed considerable attention in drug discovery. There are also substantial evidences supporting that aberrant expressions and/activities of HDAC isoforms are reported in epilepsy and HDAC inhibitors (HDACi) have been successfully utilized for therapeutic purposes in this condition. However, the specific mechanisms underlying the role of HDACs in epileptic progression have not been fully understood. Herein, we reviewed the basic information of HDACs, summarized the recent findings associated with the roles of diverse HDAC subunits in epilepsy and discussed the potential regulatory mechanisms by which HDACs affected the development of epilepsy. Additionally, we also provided a brief discussion on the potential of HDACs as promising therapeutic targets for epilepsy treatment, serving as a valuable reference for basic study and clinical translation in epilepsy field.